Interactional metadiscourse analysis of evaluative essays / Masliza Mat Zali ... [et al.] - Mat Zali, Masliza; Mohamad, Razita; Setia, Roszainora; Raja Baniamin, Raja Mariam; Mohd Razlan, Razifa (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
Metadiscourse is one of the linguistic features which helps to interact between the writer and reader and also to maintain the coherence of an essay. Every writer communicates with the reader and the writer can effectively reach his reader through metadiscourse. Since writing an essay only involved one way interaction between the writer and reader, it is a big challenge to ESL learners to write effectively and coherently. So it is interesting to study how the ESL learners produced the features of metadiscourse in their writing. In this study, an analysis of metadiscourse on a corpus of 200 evaluative essays done by UiTM Degree students from hard and soft science courses was carried on based on Hyland (2005)’s table of interactional metadiscourse. The purposes are to find out whether both groups of students use the same amount of metadiscourse and whether students from different course groups make any differences in their choice of metadiscourse as well as to investigate the most prominent and least of occurance of metadiscourse features produced by both of courses. The analysis revealed that soft science course students produced more metadiscourse features than hard science course students. It was also found that the students prominently used Selfmention and hardly found Attitude Markers in their writings. The study provides evidences as to the importance of metadiscourse in students’ writings and to create the awareness as to its usage in academic writing and also as a proposition for other cross-cultural studies.